Economics for Cambrige International AS & A Level - Bamford, Colin; Grant, Susan (London Cambridge University Press, 2021)
The coursebook provides a clear understanding of how economics operates on an international scale, while developing key skills such as analysis and evaluation. It is tailored to meet the real teaching needs of the economics classroom, incorporating feedback from extensive research, including lesson observations and teacher interview
1.Basic economic ideas and resource allocation (AS level) 2.The price system and the microeconomy (AS level) 3.Government microeconomic intervention (AS level) 4.The macroeconomy (AS level) 5.Government macroeconomic intervention (AS level) 6.International economic issues (AS level) 7.The price system and the microeconomy (A level) 7.Government microeconomic intervention (A level) 8.The macroeconomy (A level) 9.Government macroeconomic intervention (A level) 10.International economic issues (A level)
Keywords: Economics, Excercise